Depression in medical students: insights from a longitudinal study - Silva, Vanessa (2017)
Background: Factors associated with depression of medical students are poorly understood. The purpose of this study is to determine the prevalence of depression in medical students, its change during the course, if depression persists for affected students, what are the factors associated with depression and how these factors change over time. Methods: A prospective, longitudinal observational study was conducted at the Medical School of the University of Minho, Portugal, between academic years 2009-2010 to 2012-2013. We included students who maintained their participation by annually completing a questionnaire including Beck Depression Inventory (BDI). Anxiety and burnout were assessed using the State Trait Anxiety Inventory and Maslach Burnout Inventory. Surveys on socio-demographic variables were applied to evaluate potential predictors, personal and academic characteristics and perceived difficulties. ANOVA with multiple comparisons were used to compare means of BDI score. The medical students were organized into subgroups by K-means cluster analyses. ANOVA mixed-design repeated measurement was performed to assess a possible interaction between variables associated with depression. Results: The response rate was 84, 92, 88 and 81% for academic years 2009-2010, 2010-2011,2011-2012 and 2012/2013, respectively. Two hundred thirty-eight medical students were evaluated longitudinally. For depression the prevalence ranged from 21.5 to 12.7% (academic years 2009/2010 and 2012/2013). BDI scores decreased during medical school. 19.7% of students recorded sustained high BDI over time. These students had high levels of trait-anxiety and choose medicine for anticipated income and prestige, reported more relationship issues, cynicism, and decreased satisfaction with social activities. Students with high BDI scores at initial evaluation with low levels of trait-anxiety and a primary interest in medicine as a career tended to improve their mood and reported reduced burnout, low perceived learning problems and increased satisfaction with social activities at last evaluation. No difference was detected between men and women in the median BDI score over time. Conclusions: Our findings suggest that personal factors (anxiety traits, medicine choice factors, relationship patterns and academic burnout) are relevant for persistence of high levels of BDI during medical training. Medical schools need to identity students who experience depression and support then, as early as possible, particularly when depression has been present over time.